Computational trust management in economics phenomena research - Trček, Denis (Technological and Economic Development of Economy, 2018)
Economics phenomena are notably governed by dynamic, non-linear, bottom-up processes emerging from agents’ interactions. Therefore traditional top-down approaches provide a rather limited insight into these phenomena. Further, research in economics has been mostly focused on addressing tangible factors, while human agents in economic settings often do not adhere to rational reasoning, and trust is one such kind of reasoning. Thanks to recent technological advancements new approaches are enabled, and this paper proposes a novel and anticipatory research methodology for studying economics phenomena that enables inclusion of trust. The methodology, called auxiliary composite simulations, builds upon recent advancements in computational trust management. By doing so it enables bottom-up simulations of trust driven economic phenomena. The paper provides also epistemic evaluation of the methodology and ends up with an example application of the proposed apparatus.